Cardiac status of perinatally HIV-infected children: assessing combination antiretroviral regimens in observational studies. (23rd October 2018) - Williams, Paige L.; Correia, Katharine; Karalius, Brad; Van Dyke, Russell B.; Wilkinson, James D.; Shearer, William T.; Colan, Steven D.; Lipshultz, Steven E.
Abstract : Objective: To evaluate potential adverse associations of individual antiretroviral medications used in combination antiretroviral therapy regimens on cardiac structure and function in youth with perinatally-acquired HIV infection (PHIV). Design: PHIV youth ( N  = 325) enrolled in a prospective multisite cohort study had a single echocardiogram at age 7–16 years to evaluate cardiac function and structure. Methods: We applied several statistical approaches to evaluate associations between use of 18 individual antiretroviral medications with Z-scores for 11 measures of left ventricular function and structure. These included simultaneously evaluating all antiretroviral medications in adjusted linear regression models controlling for the false discovery rate (FDR), applying hierarchical models to estimate individual antiretroviral medication effects as deviations from drug class means, and evaluating latent measures of cardiac function and structure underlying multiple echocardiographic parameters. Results: Youth taking combination regimens with a protease inhibitor (69%) had significantly better cardiac function than those on other regimens. After FDR control and adjustment for other antiretroviral medications, no individual antiretroviral medication was significantly associated with any measure of left ventricular function, but zidovudine was associated with higher adjusted mean Z-scores for one measure of left ventricular structure (end-systolic wall stress). Factor analysis identified three latent factors: heart function, heart size, and heart wall stress. Lopinavir was associated with better heart function scores, whereas zidovudine was associated with higher wall stress scores. Zidovudine and nevirapine were associated with higher heart size factor scores. Conclusions: Despite cardioprotective effects of combination regimens in PHIV youth, individual antiretroviral medications were associated with altered cardiac structure, which could progress to symptomatic cardiomyopathy in adulthood. Abstract : Supplemental Digital Content is available in the text